Single tumor imaging with multiple antibodies targeting different antigens. (April 2012) - Sun, Yujing; Shukla, Girja; Pero, Stephanie C.; Currier, Erika; Sholler, Giselle; Krag, David
Antibodies are important drugs for treating cancer and there is strong rationale for using multiple antibodies to improve outcomes. We labeled two breast cancer binding antibodies, anti-ErbB2 and anti-EpCAM, with infrared fluorescence dyes of different wavelengths and determined their in vivo distribution in a breast cancer xenograft model using a near-infrared (NIR) fluorescence imaging system. Our data show that these two antibodies can be readily assessed simultaneously in mouse xenograft model. This will help guide design of dosing strategies for multiple antibodies and identify potential interaction that could affect pharmacokinetics and possible side effects.